Ethics Under Scrutiny: How Regional Notary Supervisory Assemblies Curb Professional Misconduct? - Dewisari, Carolina Gracia; Utama, I Wayan Kartika Jaya; Wesna, Putu Ayu Sriasih (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
In Indonesia, the role of the Notary Supervisory Board has a very important function in carrying out the Notary profession in carrying out its authority when violations occur or when Notaries experience problems that must be proven. The research aims to analyse the role of the Regional Notary Supervisory Council in carrying out supervision in preventing violations of the Code of Ethics by Notaries in Denpasar City and to analyse the sanctions given to Notaries who violate the Code of Ethics in Denpasar City. This research is empirical research conducted in Denpasar City because the number of notaries in this city is the highest. Data was obtained through interviews, documentation and literature study, which was then analysed descriptively qualitatively. The research results show that the Regional Supervisory Council has an important role in supervising notaries, namely checking notary protocols periodically every quarter and year, providing new notaries, as well as coordinating with the Regional Supervisory Council, and also responding to public reports with detailed verification and inspection. The Regional Supervisory Council proactively provides guidance to notaries through various programs, such as outreach regarding developments in laws and regulations, as well as monitoring the implementation of administrative obligations by notaries. The role of the Regional Supervisory Council is not only reactive in taking action against violations but also proactive in preventing violations through continuous guidance.